Performance of Tithonia diversifolia under tropical humid forest conditions - Navas Panadero, Alexander (2019)
The performance of forage banks of Tithonia diversifolia established in degraded soils, with prolonged application of agrochemicals, under humid tropical forest conditions was determined. The forage bank was established on a farm in Yopal, Casanare (Colombia). The evaluation was carried out during a year to determine the effect on the chemical characteristics and the soil macrofauna, production of green forage and dry matter, relationship between the biomass of leaf-stem and nutritional quality of the whole plant and fractions (leaf-stem). There were increases in nutrients and soil mesofauna. Likewise, differences were observed in forage production and leaf-stem ratio. The forage presented nutritional quality between acceptable and good, with the leaves being the best quality fraction. It is concluded that Tithonia diversifolia has potential for the recovery of degraded soils and adaptation to different climatic conditions, and may contribute to the production of good quality feed in strategic supplementation programs for critical periods in livestock production systems.